Circulating Structurally Related (-)-Epicatechin Metabolite Species and Levels after Sustained Intake of a Cocoa Powder High in Polyphenols Are Comparable to Those Achieved after a Single Dose - Paloma K. Barrera-Reyes (MDPI AG, 2021)
Background: While the bioavailability of cocoa polyphenols, particularly of the monomer (-)-epicatechin, has been investigated after a single-dose intake, the effect of sustained cocoa consumption on the metabolic profile of the structurally related (-)-epicatechin metabolites (SREMs) has not been investigated. Methods: A randomized, controlled crossover clinical trial in healthy young adults (18–40 year) was conducted to evaluate SREMs after consumption of a single-dose and after daily consumption of 1.3 g of polyphenol-rich cocoa powder for 28 days. The circulating SREMs were measured by ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). Results: Twenty subjects (eleven males and nine females) were enrolled. The SREMs concentrations increased to 1741 ± 337 nM after a single-dose and to 1445 ± 270 nM after sustained supplementation. Sulfate conjugates showed higher levels in females (p < 0.05). The epicatechin-3′-glucuronide (E3′G) and epicatechin-3′-sulfate (E3′S) were the most abundant metabolites in all subjects. A high intra-individual correlation (r = 0.72, p < 0.001) between SREMs concentrations after single-dose and sustained supplementation was observed. The antioxidant capacity of plasma did not change in response to the intervention and was not correlated with any of the SREMs. Conclusion: The individual SREMs profile and concentrations after a 28-day supplementation are comparable to those after a single dose.